PENGARUH DEBT TO ASSETS RATIO, DEVIDEND PAYOUT RATIO, DAN RETURN ON ASSETS TERHADAP NILAI PERUSAHAAN - Dwipayana, Made Agus Teja; Suaryana, I. Gst. Ngr. Agung (E-Jurnal Akuntansi, 2016)
This study, entitled "Effects of Debt To Asset Ratio, devidend Payout Ratio and Return On Assets Of Value Manufacturing Companies Listed in Indonesia Stock Exchange. The purpose of this study was to determine the presence or absence of the influence of Debt To Assets Ratio, devidend Payout Ratio and Return On Assets to the value of companies listed on the Stock Exchange Indonesi year period 2012-2014. The data used is secondary data obtained from the annual reports of the companies listed in Indonesia Stock Exchange 2012-2014. The population of this research is manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The sample selection using purposive sampling method and obtained a sample of 48 companies. From the test results showed that there is a positive effect of Debt To Assets Ratio, Devidend Payout Ratio and Return On Assets of the Company Value listed on the Indonesia Stock Exchange Period 2012-2014.
Keywords: Debt To Assets Ratio, Devidend Payout Ratio, Return on Assets, Firm Value